MOGO GAPII - WINARKO, GALANG BIMA PUTRA WINDURA; Artati, Anak Agung Ayu Mayun; Widnyana, Kompiang Gede (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2024)
The Mogo Gapii dance work started from a creative idea, namely Bakar Batu. It is necessary to pay attention to the limitations in order to clarify the extent of the ideas being discussed. Bakar Batu is a Papuan tradition in the form of a cooking ritual carried out together by village residents which aims to express gratitude, permission, death, bersilahturahmi (gathering of relatives and relatives, welcoming happiness (birth, traditional marriage, coronation of tribal chief), as well as to gather soldiers who died due to inter-tribal wars. This stone burning tradition is believed to have been going on for hundreds of years and is the oldest tradition in Papua. Stone burning is an original tradition of mountain tribe communities including the Agmungme, Dani, Lani, Damal, Nduga, Moni and Ekari tribes. The way to differentiate the Burning Stone Ceremony after burning between tribes from others is at the beginning of the Burning Stone ceremony itself. If the ceremony begins with men shooting pigs, then dancing together with jumping movements and circular patterns filled with shouts. which is interpreted as encouragement, it means the Stone Burning Ceremony after the tribal war. If at the beginning of Bakar Batu the men do not shoot arrows at the pig but instead immediately slaughter the pig as usual, it means that the Bakar Batu Ceremony is a ceremony such as marriage, birth, thanksgiving after the harvest and so on.